e-TuroMo: A Valuable Virtual Community Service Project for Schools Amid COVID-19 Pandemic - Chua, Christopher; Chua, Antonette (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
The COVID-19 pandemic has forced schools to adopt online teaching and other alternative delivery modes of education. Since this is an unforeseen happening, most learning institutions are not ready for this transition. This gives birth to a virtual community service project named “e-TuroMo.” In this paper, we describe the e-TuroMo project and assess its relevance. An open-ended questionnaire was distributed to gather feedback from the respondents. The project aims primarily to help schools as they try to shift from traditional classes to online teaching. It offers free services such as webinars for teachers, a course creator account on the e-TuroMo Moodle site, consultation, and technical assistance in establishing a Learning Management System (LMS). Through this project, 51 respondents have created initial online courses as an output of the webinars. Consultation sessions on online course design, delivery, and assessment were provided to some respondents. Two schools availed of technical assistance in the setup of their LMS. The respondents acknowledged the services offered by the project as timely, relevant, and valuable to their work as teachers. Overall, the results showed high admiration and approval for the project. Cost-effective software, efficient structuring of webinars based on literature, and a stable internet connection for both the organizer and participants are deemed essential when implementing a virtual community service project similar to this case.